Integrating terminological methods in a framework for collaborative development of semi-formal ontologies - Barros, Sérgio (2021)
Despite the availability of tools, resources and techniques aimed at the construction of ontological artifacts, developing a shared conceptualization of a given reality still raises questions about the principles and methods that support the initial phases of conceptualization. To tackle this issue a collaborative platform was developed where terminological and knowledge representation processes support domain experts throughout a conceptualization framework. In this article we describe the integration of a terminological method to support experts in eliciting and organizing concepts of their domain. The method is based on a linguistic analysis of textual resources with the help of a term extraction tool and by highlighting markers of relations between concepts. An application scenario is then presented to illustrate the connection between the terminological processes and the knowledge representation processes without blurring the theoretical distinction between terms and concepts.